Solve for y 12(-2)+7(y+1)=25

Math
12(-2)+7(y+1)=25
Simplify 12(-2)+7(y+1).
Tap for more steps…
Simplify each term.
Tap for more steps…
Multiply 12 by -2.
-24+7(y+1)=25
Apply the distributive property.
-24+7y+7⋅1=25
Multiply 7 by 1.
-24+7y+7=25
-24+7y+7=25
Add -24 and 7.
7y-17=25
7y-17=25
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 17 to both sides of the equation.
7y=25+17
Add 25 and 17.
7y=42
7y=42
Divide each term by 7 and simplify.
Tap for more steps…
Divide each term in 7y=42 by 7.
7y7=427
Cancel the common factor of 7.
Tap for more steps…
Cancel the common factor.
7y7=427
Divide y by 1.
y=427
y=427
Divide 42 by 7.
y=6
y=6
Solve for y 12(-2)+7(y+1)=25

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top